Public libraries’ services, potentials, opportunities and challenges in providing health information: A systematic review - Nosrat Riahinia; Ali Azimi; Davoud Haseli (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2022)
Purpose: The current research was conducted with the aim of identifying the types of services, opportunities, capacities and challenges of public libraries in providing health information from the texts of this field. Method: The research method is a systematic literature review, and the systematic study framework of Kitchenham and Charters was used to carry out it. By identifying the databases and query terms, searches were conducted and finally, by refining the sources and applying the entry and exit criteria to the research, 37 sources in English and 3 sources in Farsi were entered into the systematic review. The research tool was a checklist type. The information obtained by summarizing the contents is presented in the form of a table. Findings: The results show that the types of services include six general categories of health information, social determinants of health, health literacy education, direct provision of health services, promotion of physical mobility, and alternative and complementary care services. Capacities were categorized into four general categories: human resources, resources, library functions, and fundamental values of libraries. The opportunities included four general categories: using the capacity of other organizations, strengthening human resources, providing a place to provide health services, and increasing community resilience in crises. Finally, the challenges included: nature of the issue, libraries policy, budget, resources, equipment and technology, space, services, inter-organizational cooperation, specialized human resources, communication with clients, and client problems. Originality/Value: Considering the status of providing health information services in Iran’s public libraries’ service portfolio, awareness of the types of services, capacities, opportunities, and challenges of public libraries in the world in providing health information to citizens is useful for designing or providing health information services in Iranian libraries.